Cementless Total Hip Replacement in 20 Juveniles Using BFX™ Arthroplasty. Issue 6 (24th June 2014) - Fitzpatrick, Noel; Law, Andy Y.; Bielecki, Malgorzata; Girling, Sarah
<x xml:space="preserve">Abstract</x> Objective To describe outcome after a minimum of 1 year for total hip replacement (THR) using BioMedtrix BFX™ biologic fixation implants in skeletally immature dogs (6–10 months of age). Study Design Case series. Animals Dogs (n = 20). Methods Medical records (November 2007–June 2010) of 20 dogs, 6–10 months old that had cementless THR were reviewed. Preoperative, immediate, 6‐week and >1‐year postoperative radiographs were compared. Clinical examination was performed at 6 weeks and >1 year postoperatively. Owner questionnaire was obtained at final follow‐up. Results Cementless THR using BFX™ implants was performed because of debilitating coxofemoral pain, resulting from canine hip dysplasia, after unsatisfactory outcome with medical management. Radiographs taken immediately, 6 weeks and at a mean of 29.8 months (range, 12–48 months) postoperatively revealed satisfactory implant positioning and stability. Significant change in measured cranial–caudal femoral stem fill and level (P < .001 and P = .006, respectively) were recorded at 6 weeks postoperatively without clinical significance. No further change in stem positioning occurred. Acetabular cup orientation remained unchanged throughout follow‐up. Complications requiring further surgical intervention were not encountered. One minor superficial infection was recorded and treated. Lameness and pain on manipulation of the affected hip had greatly improved in all dogs by 6 weeks postoperatively. Conclusion Cementless THR can safely be performed in skeletally immature dogs, providing satisfactory return to normal joint function and implant survivability for at least a mean of 29.8 months.